Investigation of TEMPO partitioning in different skin models as measured by EPR spectroscopy - Insight into the stratum corneum - Elpelt, Anja; Ivanov, Daniela; Nováčková, Anna; Kováčik, Andrej; Sochorová, Michaela; Saeidpour, Siavash; Teutloff, Christian; Lohan, Silke B; Lademann, Jürgen; Vávrová, Kateřina; Hedtrich, Sarah; Meinke, Martina C (Journal of magnetic resonance (San Diego, Calif., 2020)
Electron paramagnetic resonance (EPR) spectroscopy represents an established tool to study properties of microenvironments, e.g. to investigate the structure and dynamics of biological and artificial membranes. In this study, the partitioning of the spin probe 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) in ex vivo human abdominal and breast skin, ex vivo porcine abdominal and ear skin as well as normal and inflammatory in vitro skin equivalents was investigated by EPR spectroscopy. Furthermore, the stratum corneum (SC) lipid composition (as determined by high-performance thin-layer chromatography), SC lipid chain order (probed by infrared spectroscopy) and the SC thickness (investigated by histology) were determined in the skin models. X-band EPR measurements have shown that TEMPO partitions in the lipophilic and hydrophilic microenvironment in varying ratios in different ex vivo and in vitro skin models. Ex vivo human abdominal skin exhibited the highest amount of TEMPO in the lipophilic microenvironment. In contrast, the lowest amount of TEMPO in the lipophilic microenvironment was determined in ex vivo human breast skin and the inflammatory in vitro skin equivalents. Individual EPR spectra of epidermis including SC and dermis indicated that the lipophilic microenvironment of TEMPO mainly corresponds to the most lipophilic part of the epidermis, the SC. The amount of TEMPO in the lipophilic microenvironment was independent of the SC lipid composition and the SC lipid chain order but correlated with the SC thickness. In conclusion, EPR spectroscopy could be a novel technique to determine differences in the SC thickness, thus suitably complementing existing methods.
Keywords: Skinfold Thickness; Abdomen; Humans; zevní ucho; břicho; lidé středního věku; Cyclic N-Oxides; Cellular Microenvironment; Skin barrier lipids; Female; Aged; kůže; dospělí; mladý dospělý; Breast; lipidy; spinové značení; Ear, External; senioři; lidé; zvířata; chromatografie na tenké vrstvě; Swine; Stratum corneum thickness; Epidermis; Spectrophotometry, Infrared; Adult; Electron Spin Resonance Spectroscopy; Electron paramagnetic resonance spectroscopy; ženské pohlaví; Male; TEMPO partitioning; Middle Aged; Lipids; Young Adult; Chromatography, Thin Layer; cyklické N-oxidy; Animals; buněčné mikroprostředí; spektrofotometrie infračervená; mužské pohlaví; elektronová paramagnetická rezonance; tloušťka kožní řasy; Spin Labels; epidermis; prasata; Skin; prsy